Reinforcing HIV/AIDS Prevention and Control through a Sustainable Data Management System - Demartoto, Argyo; Murti, Bhisma; Pujihartati, Sri Hilmi (Journal of Information System and Informatics, 2025)
The digitalization of healthcare services has significantly improved access to data and information regarding HIV/AIDS patients, thereby enhancing monitoring and evaluation efforts. However, discrepancies in data across various providers can lead to inefficiencies and hinder the formulation of comprehensive HIV/AIDS prevention and control programs. Therefore, integrating sustainability into healthcare service digitalization practices is essential. This research aims to explore the reinforcement of HIV/AIDS prevention and control through a sustainable data management system, using Giddens’ structuration theory as the framework. A qualitative research method with an exploratory approach was employed, including data collection through observation, in-depth interviews, Focus Group Discussions (FGD) with key informants, and document processing. The informants included the person responsible for health promotion at the Health Office of Surakarta City, members of the Regional AIDS Commission (KPAD), staff from hospitals and several public health centers (Puskesmas) in Surakarta, field officers, members of the Peer Support Group (KDS), non-governmental organizations (NGOs) involved in HIV/AIDS prevention and control, as well as HIV/AIDS patients and at-risk individuals. The research findings reveal that both people (as the agency) and institutions responsible for health data collection must collaborate to establish a sustainable data system. This collaboration ensures data accuracy and continuity, which, in turn, strengthens HIV/AIDS prevention and control programs. A sustainable data system also supports medication adherence, timely updates on patient information, and various other aspects of HIV/AIDS prevention and control.